2022
DOI: 10.1186/s12902-022-01081-9
|View full text |Cite
|
Sign up to set email alerts
|

The perirenal fat thickness was independently associated with serum uric acid level in patients with type 2 diabetes mellitus

Abstract: Background Obesity is an important risk factor for hyperuricemia. We aimed to explore the relationship between perirenal fat thickness (PrFT) and paranephric fat thickness (PnFT) and serum uric acid (SUA) in patients with type 2 diabetes mellitus (T2DM). Methods This was a cross-sectional study involving 257 patients with T2DM recruited from Beijing Luhe Hospital from September 2019 to May 2020. The basic and clinical information such as age, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“… 19 Yang et al also revealed that PrFT was independently associated with serum UA levels in T2DM. 20 Meanwhile, PrFT was also reported as an independent predictor of hyperuricemia. 21 Ke et al found that PrFT was negatively correlated with the serum HDL-c level and positively correlated with cholesterol efflux capacity in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Yang et al also revealed that PrFT was independently associated with serum UA levels in T2DM. 20 Meanwhile, PrFT was also reported as an independent predictor of hyperuricemia. 21 Ke et al found that PrFT was negatively correlated with the serum HDL-c level and positively correlated with cholesterol efflux capacity in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested that accumulation of the visceral fat was associated with increased blood uric acid [ [31] , [32] , [33] ]. Matsuura F et al suggested that visceral fat was more strongly associated with hyperuricemia than subcutaneous fat in a study of male obese subjects as early as 1998 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Composed of both brown adipose tissue and white adipose tissue, PRF is able to synthesize and secrete many adipokines, such as leptin, adiponectin, and so on [ 5 ]. PRF plays an essential role in various diseases such as hypertension [ 6 ], unilateral nephrolithiasis [ 7 ], renal cell carcinoma [ 8 ], metabolic syndrome, and atherosclerosis [ 9 ]. In addition, its role in various renal diseases has been previously proposed [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%